A case report of complicated Meckel’s diverticulum in an older adult: a diagnostic challenge - Villarreal Zavala, Rodrigo; Brito Torres, Andrea Elizabeth; Marrufo Patrón, César Augusto; Hernández Alvarado, Samuel; Pérez Valdez, Diego; Villaseñor Vidal, Jonathan (International Surgery Journal, 2025)
Meckel’s diverticulum represents a diagnostic challenge as it is often discovered incidentally during the evaluation of symptoms initially attributed to other causes or is identified as a trans-surgical finding during surgery. The three most common manifestations of symptomatic Meckel’s diverticulum are intestinal obstruction, gastrointestinal bleeding and inflammation with or without perforation. This case report discusses the complications of Meckel’s diverticulum and the importance of suspicion as a differential diagnosis in older adult patients presenting with acute abdomen.